Modelling the feasibility of bovine tuberculosis eradication in Argentina - Perez, Andres Maximiliano (2011)
The ability of countries to control and eradicate bovine tuberculosis (TB) has been jeopardised by various epidemiological and ecological features of the disease. The authors have used epidemiological modelling to develop an analytical framework to assess the likely success of a national TB eradication programme in Argentina. Study results suggest that the current control programme is financially feasible in the long term. However, considering that the costs of the TB eradication programme in Argentina are entirely borne by the producer, the initial investment required and the long-term horizon needed to gain revenue may prevent producers from endorsing the programme. Regionalised programmes that allow differential control strategies to be implemented in specific regions may increase the likelihood of success. This methodological approach could be extended to design and evaluate control and eradication programmes for TB and other infectious diseases in other regions of the world.